The Arteriovenous Fistulas for Hemodialysis Complications in Short and Long Term in Department of Cardiovascular Surgery Clinic, Turgut Ozal Medical Center. (Annals of Medical Research, 2021)
None
Keywords: Arteriovenous Fistula; Chronic Renal Failure; Complication.